Penerapan Metode Multidimensional Scaling (MDS) dalam Perencanaan Formulasi Strategi Pemasaran Supermarket Hero Malang - Sugeng Santoso (Jurnal Teknik Industri, 2000)
Customer value is customer's believeing  to the most important atributes of supermarket. Those  are all about  marketing  mix atributes  such  as cost,  product,  distribution,  and promotion. Customer's  value   can  be  found  with   implementing  Multidimensional   Scaling  Method   that spreading questionnaires and interviewing to have initial data.This  research  used Multidimensional  Scaling  Method  to know  customer's  demand  to supermarkets.  This  can  be  used  as  a beginning  standart  in  marketing  strategy  planning.  This method  result  a perception map that  drawing challanging  situation among the  supermarket  that viewed from marketing mix atributes.The result of analysis conclude that demand or the most customer's  important  atributes for  choosing  supermarket  is  cost  atribute  and  distribution.   In  Hero  Supermarket,   customer's demand is in product atribute that it's  items are good quality  product and variety that Hero standed in Kuadran  I. To get customers I market segmentation to marketing  strategy formulation  is  :    if in area  CI, Hero  supermarket  have a competition with  Alfa Supermarket,   so that  should  stress it's strategy  in cost  atribute.  It's also in area  III, Hero  Supermarket  and Ratu  Supermarket  have  a competition  in  cost  atribute.  And  in  area  IV,  a  competition  happen  among  Hero,  Mitra,  and Matahari departement  store in distribution and promotion  atribute.